Applying Transdisciplinary Thinking to Pastoral Livelihoods and Environments - Keith Woodford; Xiaomeng Lucock; Derrick Moot (Animals, 2025)
Transdisciplinary thinking lies at one end of a continuum within system thinking, with discipline-based approaches at the other end. Interdisciplinarity and multidisciplinarity are intermediate domains within this continuum. Transdisciplinary thinking is unique in always starting with problem-structuring related to contexts, in which people, typically with multiple and competing objectives, interact with a biophysical world. As such, transdisciplinary thinking is particularly relevant to pastoral systems where livelihoods and environmental issues intersect, and where multiple stakeholders are the norm. Integration, both within transdisciplinary thinking and consequent action, is particularly challenging. This is because there is no quantitative methodology that can capture the complex essence of transdisciplinary issues that encompass both human and biophysical disciplines. Nevertheless, a transdisciplinary approach provides a framework for civilised debate and communication within a broad framework of policy generation. We illustrate these issues with two highly contrasting studies, these being pastoralism at the country level in New Zealand and at the county level in Qinghai on the Qinghai-Tibet Plateau in Western China. Both case studies are characterised by complex property rights within a dynamic resource-constrained environment, in which environmental issues have planetary implications that extend well beyond the bounds of the pastoral system itself.